Formalized design and synthesis of parallel programs for videographic shortcuts - Doroshenko, A.Yu.; Beketov, O.G.; Zhereb, K.A.; Yatsenko, О.A. (Інститут програмних систем НАН України, 2025)
Prombles in programming 2013; 3: 38-46